Reservas internacionais para o Brasil: Custos fiscais e patamares ótimos - Christian Vonbun (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This paper shows estimates of the optimal level of foreign reserves for Brazil between the first quarter of 1998 and the same trimester of 2008, by applying the Jeanne e Ranciére (2006) framework, using different scenarios. We also estimate the fiscal costs of holding this asset, as well as the eventual excessive costs or savings due to differences between the actual and the optimal reserves holdings, kept by the Brazilian Central Bank (BCB). Our results suggest that, under various alternative scenarios and assumptions regarding the model's main parameters, the observed level of reserves in Brazil has become above the optimal level, thereby generating high and increasing costs for the Brazilian government and tax payers.
Keywords: E63; F31; F32; F34; F40; F41; G11; 330; Währungsreserven; Brasilien